Dynamic CT imaging of volumetric changes in pulmonary nodules correlates with physical measurements of stiffness. Issue 2 (February 2017) - Lartey, Frederick M.; Rafat, Marjan; Negahdar, Mohammadreza; Malkovskiy, Andrey V.; Dong, Xinzhe; Sun, Xiaoli; Li, Mei; Doyle, Timothy; Rajadas, Jayakumar; Graves, Edward E.; Loo, Billy W.; Maxim, Peter G.
Abstract: Background and purpose: A major challenge in CT screening for lung cancer is limited specificity when distinguishing between malignant and non-malignant pulmonary nodules (PN). Malignant nodules have different mechanical properties and tissue characteristics ('stiffness') from non-malignant nodules. This study seeks to improve CT specificity by demonstrating in rats that measurements of volumetric ratios in PNs with varying composition can be determined by respiratory-gated dynamic CT imaging and that these ratios correlate with direct physical measurements of PN stiffness. Methods and materials: Respiratory-gated MicroCT images acquired at extreme tidal volumes of 9 rats with PNs from talc, matrigel and A549 human lung carcinoma were analyzed and their volumetric ratios ( δ ) derived. PN stiffness was determined by measuring the Young's modulus using atomic force microscopy (AFM) for each nodule excised immediately after MicroCT imaging. Results: There was significant correlation ( p  = 0.0002) between PN volumetric ratios determined by respiratory-gated CT imaging and the physical stiffness of the PNs determined from AFM measurements. Conclusion: We demonstrated proof of concept that PN volume changes measured non-invasively correlate with direct physical measurements of stiffness. These results may translate clinically into a means of improving the specificity of CT screening for lung cancer and/or improving individual prognostic assessments based on lung tumor stiffness.